Analogy: the universal switch of Schopenhauerian thought - Batini, Ugo (Voluntas: Revista Internacional de Filosofia, 2022)
Often perceived by its contradictors as the main fragility of its system, analogy constitutes however a driving element of the development of Schopenhauerian metaphysics, and makes it possible to avoid the pitfall of theoretical egoism in which any idealistic philosophy can sink. We will try to show, in accordance with the indications of paragraph 19 of The World as Will and Representation, how Schopenhauer understands the totality of the phenomena "by analogy with our body" and establishes the structure of his masterpiece from this analogical dynamic that puts in motion the primitive intuition of his thought.